Polystyrene Pocket Lithography: Sculpting Plastic with Light (Adv. Mater. 27/2022). Issue 27 (7th July 2022) - Samal, Pinak; Samal, Jay Rabindra Kumar; Gubbins, Eva; Vroemen, Pascal; van Blitterswijk, Clemens; Truckenmüller, Roman; Giselbrecht, Stefan
Abstract : Photolithography In article number 2200687, Pinak Samal, Stefan Giselbrecht, and co‐workers present an economical and easily accessible direct deep‐UV photolithography method for fabricating microstructures directly in tissue‐culture substrates while requiring minimal processing time. The remarkable straightforwardness of the process enables this class of microengineering techniques to be broadly accessible to diverse research communities.